A Realist Evaluation of the Use of European Funds To Address the Needs of Young People in NEET Situation in Romania - Lonean, Irina (Calitatea Vieții, 2025)
In 2023, Romania recorded the higher percentage of young people (15−29 years old) in EU who were neither in employment nor in education and training (NEET): 19.3%. Almost no progress was made between 2014 and 2023, despite substantial funding available within the Human Capital Operational Programme 2014−2020, over EUR 430 million, the existence of the EU Youth Guarantee policy framework and the commitment of the Romanian Government to address the problem. The article presents a realist evaluation approach and builds upon the findings of the evaluations of the Human Capital Operational Programme, focusing on explaining the limited sustainable results delivered for young people in the NEET situation. It asks what contextual factors and mechanisms contributed to the programme results and what is explaining the shortcomings in achieving the planned targets. Findings underline that limited outcomes are explained by substantial delays, associated with political instability and institutional capacity issues, legislative bottlenecks, the limited flexibility of funding management, restrictive or too ambitious requirements from projects, the limited adaptation of support provided to the needs of young people in the NEET situation, especially to the needs of young women.